The Role of Pesantren Education in Preparing Students to be Globally Competitive and Have Noble Morals - Nunung Dwi Setiyorini; Muslikhul Ibad (Lembaga Yasin AlSys, 2025)
This study analyzes the role of Pondok Pesantren Al Ulya Kendal in preparing santri (students) to achieve global competitiveness while maintaining noble character in the context of 21st-century technological advancement and globalization. Employing a qualitative case study approach, data were gathered through interviews, observations, and documentation at Pondok Pesantren Al Ulya Kendal. The findings reveal a comprehensive educational strategy encompassing three key dimensions: (1) curriculum integration that blends religious and general education using interactive methods such as sorogan, bandongan, group discussions, and collaborative projects; (2) character formation through habituation and role modeling, emphasizing daily discipline, independence, regular worship, and the exemplary conduct of kyai and ustadz; and (3) the cultivation of 21st-century competencies and leadership skills via programs such as muhadharah (speech training), student organizations (OPPM), and digital literacy initiatives. While challenges such as limited technological infrastructure and resource constraints persist, the pesantren leverages strong alumni networks and community support to sustain its mission. The study concludes that Pondok Pesantren Al Ulya effectively nurtures intellectually capable, morally grounded, and globally adaptable individuals, demonstrating that Islamic educational institutions can harmonize tradition with modernity to meet contemporary global demands.